Peak athletic performance and ageing: Evidence from baseball - Bradbury, J. C. (Journal of Sports Sciences, 2009)
Baseball players exhibit a pattern of improvement and decline in performance; however, differing lengths of careers and changes in rules and characteristics of the game complicate assessments of age-related effects on performance. This study attempts to isolate the impact of age on several player skills while controlling for relevant outside factors using longitudinal data from 86 seasons of Major League Baseball. The results indicate that players age in different skills in accord with studies of ageing in other athletic contests. For overall performance, multiple-regression estimates indicate that hitters and pitchers peak around the age of 29 - later than previous estimates. Athletic skills such as hitting and running peak earlier than skills that rely heavily on experience and knowledge, such as issuing and drawing walks.